Analisis Korelasi Neutrophil-Lymphocyte Ratio (NLR) dengan Indikator Komplikasi Makrovaskular dan Mikrovaskular pada Diabetes Melitus Tipe 2 - Hasanah, Fathul Hidayatul; Wahyuni, Sri; Primartati, Danny Meganingdyah; Fatmariza, Aulia Risqi; Sari, Fita (Biocaster : Jurnal Kajian Biologi, 2025)
Type 2 Diabetes Mellitus (DM type 2) is associated with low-grade systemic inflammation. Neutrophil-Lymphocyte Ratio (NLR) is a pro-inflammatory and oxidative stress biomarker in cardiometabolic diseases such as T2DM. This study aims to analyze the relationship of NLR with leukocyte count, random blood glucose, creatinine, total cholesterol, Serum Glutamic Pyruvic Transaminase (SGPT), and Serum Glutamic Oxaloacetic Transaminase (SGOT). The study design is a retrospective analysis with respondents of 162 uncomplicated T2DM patients treated at Mojowarno Christian General Hospital, Jombang. The results of the study showed that the average number of leukocytes was 12,688 cells/µl, neutrophils 75.3%, lymphocytes 17.2%, NLR 8.5, blood glucose 273.2 mg/dl, SGOT 40.88 U/l, SGPT 54.64 U/l, total cholesterol 196.3 mg/dl (<200), and creatinine 1.13 mg/dl. Correlation tests showed that NLR was significantly associated with leukocyte count (p = 0.000 < 0.05) and total cholesterol (p = 0.000 < 0.05), but not significantly correlated with random blood glucose (p = 0.064 > 0.05), SGOT (p = 0.089 > 0.05), SGPT (p = 0.929 > 0.05), or creatinine (p = 0.625 > 0.05). In conclusion, in patients with type 2 diabetes, NLR was significantly correlated with leukocyte count and total cholesterol, but not with random blood glucose, SGOT, SGPT, or creatinine.